2016
DOI: 10.1590/0034-737x201663030015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito de doses e fontes de nitrogênio sobre variáveis morfológicas, interceptação de radiação e produtividade do girassol

Abstract: RESUMO Objetivou-se, com este trabalho, avaliar o efeito de doses e de fontes de nitrogênio sobre as variáveis morfológicas relacionadas com a produtividade de dois cultivares de girassol. O delineamento utilizado foi o de blocos ao acaso, em esquema fatorial 5 x 2 x 2, com cinco doses de adubação nitrogenada (0, 40, 80, 120 e 160 kg ha-1), duas fontes de nitrogênio (N), fertilizante convencional (ureia), com 44% de N e fertilizante nitrogenado de liberação lenta, com 26% de N, e dois cultivares de girassol (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…A similar response had [21], which found a quadratic effect of nitrogenous fertilization in clonal seedlings of cocoa. [16], verified the nitrogen fertilization has contributed positively to the initial development of seedlings of Umbuzeiro, demonstrated by an increase in leaf area and in other parameters as well as similar results found for [29] in Sunflower.…”
Section: Fig 3: the Diameter Of The Stem Of The Cupuaçu Tree Seedlinsupporting
confidence: 78%
“…A similar response had [21], which found a quadratic effect of nitrogenous fertilization in clonal seedlings of cocoa. [16], verified the nitrogen fertilization has contributed positively to the initial development of seedlings of Umbuzeiro, demonstrated by an increase in leaf area and in other parameters as well as similar results found for [29] in Sunflower.…”
Section: Fig 3: the Diameter Of The Stem Of The Cupuaçu Tree Seedlinsupporting
confidence: 78%
“…Tomich et al (2003) found plant height of 2.05 m, whereas Biscaro et al (2008) estimated that the N dose of 73 kg ha -1 was associated with plant height of 1.15 m, which is inferior to the value found in the present study for a similar N dose (Figure 1). On the other hand, Schwerz et al (2016) did not observe effect of N fertilization on sunflower height.…”
Section: Resultsmentioning
confidence: 63%
“…The LAI is the main factor responsible for determining the solar interception rate of a culture (29) . However, the radiation interception depends on other factors besides the LAI, such as the number, size and angle of leaves, the weather, and the management practices (30) .…”
Section: Resultsmentioning
confidence: 99%